lncRNA IGHCγ1 Acts as a ceRNA to Regulate Macrophage Inflammation via the miR-6891-3p/TLR4 Axis in Osteoarthritis - Pengjun Zhang; Jianmei Sun; Caihong Liang; Bingjie Gu; Yang Xu; Hongying Lu; Bo Cao; Hao Xu (Mediators of Inflammation)
Accumulating data have implicated that long noncoding RNA (lncRNA) plays an important role in osteoarthritis (OA), which may function as a competitive endogenous RNA (ceRNA) of microRNAs (miRNAs). lncRNA IGHCγ1 has been demonstrated to regulate inflammation and autoimmunity. Nonetheless, the altering effect of IGHCγ1 in OA remains unclear. This study is aimed at investigating the mechanism and function of lncRNA IGHCγ1 in OA. CCK-8, EdU, and transwell assays were used to estimate macrophage proliferation and migration. Fluorescence in situ hybridization (FISH) was performed to estimate the local expression of lncRNA IGHCγ1 in macrophages. Luciferase reporter assay was adopted to validate the ceRNA role of IGHCγ1 as miRNA sponge. lncRNA IGHCγ1 was primarily localized in macrophage cytoplasm and upregulated in OA. miR-6891-3p inhibited macrophage proliferation, migration, and inflammatory response by targeting TLR4, while lncRNA IGHCγ1 promoted TLR4 expression by functioning as a ceRNA for miR-6891-3p through the NF-κB signal in macrophages. This study strongly supports that lncRNA IGHCγ1 regulates inflammatory response via regulating the miR-6891-3p/TLR4/NF-κB axis in macrophages.